FARS2 Causing Complex Hereditary Spastic Paraplegia With Dysphonia: Expanding the Disease Spectrum. (September 2019) - Forman, Eva B.; Gorman, Kathleen M.; Ennis, Sean; King, Mary D.
Herein we present two siblings with hereditary spastic paraplegia caused by novel compound heterozygous variant and deletion in FARS2 and expansion of the disease spectrum to include dysphonia.